Rubber legs and white tail-hairs - McManus, Patrick F. (Holt, 1987)
Collection of humorous stories about the outdoors includes "Muldoon in love," "Cry Wolf," "Pip," "The MFFFF," "Summer reading," and "Angler's dictionary.".